Research progress of connexin 43 in cardiovascular diseases - Zhao Xinxin; Han Pan; Li Qiao (Frontiers in Cardiovascular Medicine)
Gap junctions (GJs) are critical structures for cardiac electrical signal conduction and synchronized contraction. Their fundamental components are transmembrane proteins from the connexin (Cx) family, which assemble into hexameric channels to form intercellular ion-permeable pathways, ensuring efficient electrical transmission and coordinated contraction between cardiac cells. Connexin 43 (Cx43), the most abundant connexin in the heart, serves as the primary constituent of ventricular gap junctions. Alterations in the structure, expression, distribution, and phosphorylation levels of Cx43 are closely associated with various cardiac pathologies, including arrhythmias, myocardial infarction, heart failure, ischemic cardiomyopathy, and diabetic cardiomyopathy. Thus, in-depth investigations into the biological characteristics of Cx43 are essential for elucidating the mechanisms underlying these diseases and developing potential therapeutic strategies. This review summarizes the role of Cx43 in cardiac diseases, explores its functional changes under electrophysiological and pathological conditions, and evaluates its impact on disease progression, providing theoretical insights for mechanistic studies and clinical interventions in cardiovascular diseases.